Prediction of flexural and shear yielding strength of short span I-girders with concrete-filled tubular flanges and corrugated web - II: Numerical simulation and theoretical analysis. (March 2020) - Wang, Y.M.; Shao, Y.B.; Chen, C.; Katwal, U.
Abstract: Currently, finite element (FE) model is built for analyzing the shear performance of I-girder with concrete-filled tubular flanges (CFTFs) and corrugated web (CW). The accuracy of the built FE model is verified through comparison with experimental results. The failure mechanism of the composite I-girder is investigated from the FE simulations. Based on such failure mechanism, theoretical analyses are carried out to deduce equations for predicting the flexural strength of the CFTFs and the shear yielding strength of the CW. The presented equations are then evaluated, to ensure their accuracy and reliability, through comparisons with experimental results and a parametric study of 30 FE models. From the presented equations, it is found that the shear stress still distributes uniformly along the web height and the bending moment is completely sustained by the CFTFs. However, it is not suitable to assume that all of the shear force is sustained by the corrugated web because the CFTFs also sustain about 12% of the shear force. Highlights: Finite element model was built and verified to analyze I-girders with concrete-filled tubular flanges and corrugated web. Theoretical equation was deduced and presented to predict flexural yielding strength of the composite I-girder. Theoretical equation was deduced and presented to predict the shear yielding strength of the corrugated web in the composite I-girder.